Communicating to Influence Perceptions of Social Stigma: Implications for the Use of Signs by the Homeless as a Means of Soliciting Funds. (October 2016) - Boster, Franklin J.; Liu, Rain Wuyu; Poorisat, Thanomwong; Cheng, Ying; Kim, Wonkyung; Salmon-Seidmann, Nicholas D.; Salmon, Charles T.
Homelessness is an important social problem in many countries, including the United States. The plight of the homeless is compounded by a high level of stigma associated with the homeless. This study examines the effects of humorous and nonhumorous signs used by the homeless to attract donations. Study 1 shows that nonhumorous signs attracted 10 times as much money as humorous signs. Study 2 shows that subjects felt more comfortable in the presence of homeless not holding a sign and perceived them more positively compared with homeless holding a humorous sign. Positive perceptions of them led to more comfort, which led to more donations. Study 3 shows that subjects perceived homeless not holding a sign more positively compared with homeless holding a nonhumorous sign. These findings suggest that signs make potential donors feel uncomfortable, potentially resulting in diminished donations.